Respuesta :
in form
ax+by=c
slope=-a/b
y intercpept=c/b
so
-3x-4y=-12
a=-3
b=-4
c=-12
slope=-(-3)/-4=3/-4=-3/4
yint=-12/-4=3
slope=-3/4
yint is 3
ax+by=c
slope=-a/b
y intercpept=c/b
so
-3x-4y=-12
a=-3
b=-4
c=-12
slope=-(-3)/-4=3/-4=-3/4
yint=-12/-4=3
slope=-3/4
yint is 3
For this you want to put it into slope-intercept form: y=mx+b
-3x-4y=-12
add over -3x
-4y=3x-12
divide by -4
y=-3/4x + 3 (now it's in the right form!)
The slope is m (-3/4)
and the y intercept is b (3)
-3x-4y=-12
add over -3x
-4y=3x-12
divide by -4
y=-3/4x + 3 (now it's in the right form!)
The slope is m (-3/4)
and the y intercept is b (3)